Book review: Mark Swilling, The Age of Sustainability: Just Transitions in a Complex World. (November 2022) - Arvind, Jasmitha
Mark Swilling, The Age of Sustainability: Just Transitions in a Complex World . Routledge, 2019, 350 pp., £31.49 (eBook). ISBN: 978-0-429-05782-3